PENGARUH PRODUCT PRICE, INDIVIDUAL PERSONALITY DIFFERENCES, ENVIRONMENTAL FRIENDLINESS PADA KEPUTUSAN PEMBELIAN - Rina Astini; Yuyus Yustian K (MIX: JURNAL ILMIAH MANAJEMEN, 2020)
The purpose of this study was to determine the effect of Product Price, Individual Personality Differences on Environmental Friendliness of Isotonik Drink “Isoplus”. The population used in this research are runners who practice at GOR Soemantri. Sampling method in this research was conducted by questionnaire and by used probability sampling method. The sample in this study used the theory of Hair et al. (2008), who recommend samples to be taken in this research based on the number of items of statements multiplied by 5-10, namely 29 x5 = 145, then rounded up to 150 respondents. Data analysis method used in this study is SEM (Structural Equation Model) using Lisrel. The results showed that Product Price had a positive and significant effect on Consumer Purchase Decisions, whereas Individual Personality Differenceand Environmental Friendliness had no significant effect on Consumer Purchase Decisions.